Changes in extreme poverty in Bangladesh (2000–2015): Trend, dynamics, and implications for research and interventions - BRAC Institute of Governance and Development (Practical Action Publishing, 2022)
This article was published in Enterprise Development & Microfinance and the definite version is available at: http://doi:10.3362/1755-1986.18-00002 The Article's website is at: https://practicalactionpublishing.com/article/2080/changes-in-extreme-poverty-in-bangladesh-20002015-trend-dynamics-and-implications-for-research-and-interventions